Association of Neutrophil to High-Density Lipoprotein Cholesterol Ratio with Cardiac Ultrasound Parameters and Cardiovascular Risk: A Cross-Sectional Study Based on Healthy Populations - Pan X; Zhang X; Ban J; Yue L; Ren L; Chen S (Dove Medical Press, 2023)
Xiaoyu Pan,1,2 Xueqing Zhang,2 Jiangli Ban,2 Lin Yue,3 Lin Ren,2 Shuchun Chen1,2 1Department of Internal Medicine, Hebei Medical University, Shijiazhuang, Hebei, People's Republic of China; 2Department of Endocrinology, Hebei General Hospital, Shijiazhuang, Hebei, People's Republic of China; 3Department of Endocrinology, the Third Hospital of Shijiazhuang, Shijiazhuang, Hebei, People's Republic of ChinaCorrespondence: Shuchun Chen, Department of Internal Medicine, Hebei Medical University, People's Republic of China, Tel +86 31185988406, Email chenshuc2014@163.comBackground: Neutrophils and high-density lipoprotein cholesterol (HDL-C) are significantly linked to cardiovascular disease (CVD). This study investigates the correlation of neutrophil count to HDL-C ratio (NHR) with cardiac ultrasound parameters and cardiovascular risk in healthy populations.Materials and Methods: Firstly, NHR was calculated based on neutrophils and HDL-C. Then, the differences in basic clinical characteristics and cardiac ultrasound parameters were compared between the high and low NHR groups, males and females. Subsequently, cardiovascular risk was predicted according to the Chinese 10-year ischemic cardiovascular disease (ICVD) risk assessment tool for people aged 35- 60 years. Finally, the correlation between NHR and cardiac ultrasound parameters and cardiovascular risk was calculated.Results: A total of 3020 healthy participants, 1879 males and 1141 females, were included. Participants in the high NHR group had significantly increased Aorta (AO), Left Atrium (LA), Right Atrium (RA), Right Ventricle (RV), End Systolic Diameter of Left Ventricle (ESD), End Diastolic Diameter of Left Ventricle (EDD), Main Pulmonary Artery (MPA), Right Ventricular Outflow Tract (RVOT), Interventricular Septum (IVS), Left Ventricular Posterior Wall (LVPW), and cardiovascular risk and decreased E/A values compared to those in the low NHR group. The same results were found in males participants compared to females. A total of 1670 participants underwent ICVD risk assessment tool. Cardiovascular risk was significantly higher in those with high NHR and in males than in those with low NHR and in females. Correlation analysis showed that NHR was positively correlated with AO, LA, RA, RV, ESD, EDD, MPA, RVOT, IVS, LVPW and cardiovascular risk, and negatively correlated with E/A values.Conclusion: Our study demonstrates that NHR is significantly associated with cardiac ultrasound parameters and cardiovascular risk in healthy populations. NHR may serve as a useful indicator for the early diagnosis and treatment of cardiovascular disease among healthy populations.Keywords: neutrophils, high-density lipoprotein cholesterol ratio, cardiovascular risk, cardiac ultrasound, cardiovascular disease